You will meet a tall dark stranger [videorecording (DVD)] - Allen, Woody, 1935-; Allen, Woody, 1935-; Hopkins, Anthony, 1937-; Pinto, Freida, 1984-; Jones, Gemma; Brolin, Josh; Watts, Naomi, 1968-; Banderas, Antonio (Sony Pictures Home Entertainment, 2011)
After Alfie leaves his wife, Helena, to pursue his lost youth with a free-spirited call girl named Charmaine, Helena abandons rationality and surrenders her life to the loopy advice of a charlatan fortune teller. Meanwhile, daughter Sally develops a crush on her handsome boss, Greg, while her husband, Roy, becomes moonstruck over Dia, a mystery woman who catches his gaze through a nearby window. These four will find out how easy it is for their illusions to make fools of them.